SATISFACTION OF PATIENTS WITH THE QUALITY OF MEDICAL EXAMINATION AND TREATMENT SERVICES AT DISTRICT HOSPITALS, THANH HOA PROVINCE, YEAR 2020-2021 (Vietnam Journal of Community Medicine, 2022)
Background: The quality of medical services in general and medical examination and treatmentservices in particular are always interested and continuously improved by hospitals, especiallydistricts hospitals.Objectives: Describe the satisfaction of patients and their relatives with the quality of medicalexamination and treatment services at district hospitals.Methods: Cross-sectional survey, quantitative research.Results: This study collected information from 420 patients and their relatives at 6 districtshospital, Thanh Hoa province through questionnaires. The results showed that the quality scoreand satisfaction rate of patients were quite high, with scores and rates respectively (3.63 - 4.26points) and (72.6% - 85.2%).
Keywords: Satisfaction, Medical examination and treatment services, Patients.